Como resolver as seguintes equações usando a lei do anulamento do produto ?
a)x(x+1)=0
b)2x(x-5)+0
Soluções para a tarefa
Respondido por
2
a) x(x+1)=0
x = 0
x+1 = 0 ⇔ x = -1
b)2x(x-5)=0
2x = 0 ⇔x = 0
x-5 = 0 ⇔x = 5
x = 0
x+1 = 0 ⇔ x = -1
b)2x(x-5)=0
2x = 0 ⇔x = 0
x-5 = 0 ⇔x = 5
Respondido por
0
a)x(x+1)=0
x = 0
x + 1 = 0 ==> x = - 1
b)2x(x-5)=0
2x = 0 ==> x =0
x - 5 = 0 ==> x = 5
Perguntas interessantes
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás